2022
DOI: 10.1186/s13063-022-06368-9
|View full text |Cite
|
Sign up to set email alerts
|

A cluster-randomized trial of a complex intervention to encourage deprescribing antidepressants in nursing home residents with dementia: a study protocol

Abstract: Background The effectiveness of psychotropic medication on behavioral and psychological symptoms of dementia (BPSD) is limited, while associated with a higher risk of adverse events. Non-pharmacological treatment of BPSD is advocated as treatment of first choice. However, many general practitioners (GPs) find it difficult to initiate deprescribing, and when attempting to discontinue psychotropic medication in nursing home residents, they face many barriers. Therefore, we hypothesize that an int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Ongoing work in the field of SDM in LTC includes a Danish complex intervention using health-care provider education, a reflection tool for staff to evaluate symptoms, and a dialog tool to facilitate conversations with residents/caregivers about use of psychotropic medications in residents with dementia. ( 27 ) Future implementation efforts for SDM likely requires this type of active complex intervention, including supports such as education/training for health-care providers, staff and residents/caregivers, coaching/facilitation, decision-support tools and other structures to facilitate SDM.…”
Section: Discussionmentioning
confidence: 99%
“…Ongoing work in the field of SDM in LTC includes a Danish complex intervention using health-care provider education, a reflection tool for staff to evaluate symptoms, and a dialog tool to facilitate conversations with residents/caregivers about use of psychotropic medications in residents with dementia. ( 27 ) Future implementation efforts for SDM likely requires this type of active complex intervention, including supports such as education/training for health-care providers, staff and residents/caregivers, coaching/facilitation, decision-support tools and other structures to facilitate SDM.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed description of the main trial and the development of the intervention is reported elsewhere [ 32 , 37 ]. To summarize, the trial was conducted as a cluster randomized controlled trial with GPs working as nursing home physicians as the clusters.…”
Section: Introductionmentioning
confidence: 99%